2015
DOI: 10.1021/acs.chemrestox.5b00127
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Investigation of the Thyroid Hormone Activity of Hydroxylated Polybrominated Diphenyl Ethers

Abstract: Polybrominated diphenyl ethers (PBDEs) have been shown to have a disruptive effect on the thyroid hormone system, and one possible mechanism is the direct binding of their hydroxylated metabolites (HO-PBDEs) to thyroid hormone receptors (TRs). However, the experimental data on the thyroid hormone activity of HO-PBDEs are limited, and the molecular interaction mechanism remains unclear, impeding the ecological risk assessment for these widespread contaminants. In the present research, a quantum chemical approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…However, its C−Br bonds are less activated than expected compared to the penta‐ and hexabrominated compounds, considering its more favorable Δ E +ZPE, because the C−Br* character is delocalized over all C−Br bonds in the LUMO. In addition, for a study of THRβ (which is involved in binding T 3 ), increasingly brominated PBDEs/OH‐BDEs caused a steady increase in overall inhibition, a trend similar to our computational results albeit for different types of XB interactions …”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…However, its C−Br bonds are less activated than expected compared to the penta‐ and hexabrominated compounds, considering its more favorable Δ E +ZPE, because the C−Br* character is delocalized over all C−Br bonds in the LUMO. In addition, for a study of THRβ (which is involved in binding T 3 ), increasingly brominated PBDEs/OH‐BDEs caused a steady increase in overall inhibition, a trend similar to our computational results albeit for different types of XB interactions …”
Section: Resultssupporting
confidence: 85%
“…Br···Se XB interactions with MeSe À were modeled foras et of four PBDEs used by Roberts et al [10] and 18 OH-BDEs in Yu et al (Figure 5). [28] XB complexes are designated by the ring position at which XB takes place (o, m,o rp)u sing ap rime for interactions to the ring opposite the hydroxyl group. For example,f or XB-o'À À3a-HO-BDE-7,X Bo ccurs at the ortho position of 3a-HO-BDE-7 on the ring opposite the hydroxyl group.…”
Section: Xb Interactions With Pbdessupporting
confidence: 89%
See 2 more Smart Citations
“…For example, five monohydroxy tetra‐BDE metabolites of BDE‐47 were identified in rodents (rat and mouse) . Many studies have shown that OH‐PBDEs altered or enhanced toxicological effects compared with PBDEs, such as the ability to disrupt thyroid hormone homeostasis and sex hormone steroidogenesis as well as neurotoxicity . At present, the toxicity of pollutants such as PBDEs introduced into the blood stream during environmental exposure to industrial pollutants is a real concern.…”
Section: Introductionmentioning
confidence: 99%